Mary Shelley [videorecording (DVD)] - Al-Mansour, Haifaa, 1974-; Al-Mansour, Haifaa, 1974-; Fanning, Elle, 1998-; Booth, Douglas, 1992-; Dillane, Stephen, 1956- (Shout! Factory, 2018)
Dramatizes the life of Mary Shelley, author of Frankenstein, and her love affair with poet, Percy Shelley.